A STUDY ON JUNIOR HIGH SCHOOL STUDENTS’ ABILITY IN COMPREHENDING NARRATIVE TEXT - Santiya Santiya; Rumiri Aruan; Indah Tri Purwanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Narrative text is one of the types of text learned in school. Therefore, it is necessary to know the students’ ability in comprehending narrative text. The aim of this study is to find out the ability in comprehending narrative text of the third year of Junior High School 1 Sungai Apit which consists of 82 students in total. The writer used cluster random sampling technique to determine the sample. The samples were 30 students. The instrument was a test which consisted of 40 items. The frame of the test covers 8 components: main idea, reference, detailed information, vocabulary, inference, social functions, generic structures, and language features. The findings show that the ability in comprehending narrative text of third year of Junior High School 1 Sungai Apit was high level with mean score 83.The highest mean score (80) was in language features and the lowest mean score (51.3) was in determining main idea. However, the students are suggested to expand their ability of the eight components in comprehending narrative text for the better results. Furthermore, the teachers are expected to be able to provide better teaching and learning to improve students’ reading comprehension abilities.Key Words: Ability, Reading comprehension, Narrative text